Beyond Representations: Photographs in Archaeological Knowledge - Guha, Sudeshna (Complutum, 2013)
In attending to the intervention of photography within archaeological practices in South Asia the article reckons with the material which is a photograph, and its social materiality within constructs of archaeological knowledge. It draws attention to creations of evidentiary domains and their shifting representations. Visual histories permit disciplinary introspection by facilitating reflexive praxis. They encourage us to think of the ways in which we historicise the past, write about histories of archaeological practices, and establish notions of evidence. By highlighting the unique agency of photographs and their collections through their multiple life histories, the aims here are to demonstrate the importance of engaging with issues of historiography, and the dominant ontology of the visual in sustaining archaeological intent, both of which are often glossed over by theorists of archaeology.